Gestational trophoblastic neoplasia presenting as an interstitial ectopic pregnancy - C. Toal; A.A. Garrett; S. Kostadinov; M. Boisen (Elsevier, 2021)
Gestational trophoblastic disease (GTD) is a group of benign and malignant tumors that develop from placental tissue and includes hydatidiform moles and gestational trophoblastic neoplasia (GTN). Invasive molar disease and choriocarcinoma are rare forms of GTN and can arise from any pregnancy event. An interstitial ectopic pregnancy occurs with implantation within the intramural portion of the fallopian tube covered by myometrium. We present two cases of an invasive mole with pathology consistent with choriocarcinoma in situ arising from an interstitial ectopic pregnancies. We review management strategies including a minimally invasive surgical approach. Additionally we present a review of the literature of gestational trophoblastic disease associated with interstitial ectopic pregnancies.